2015
DOI: 10.1007/s11032-015-0242-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SNPs linked to eight apple disease resistance loci

Abstract: Although genetic and genomic studies have progressed to a very advanced level in apple, the application of this acquired knowledge for markerassisted breeding (MAB) remains limited mainly to pyramiding monogenetically inherited resistances against apple scab, powdery mildew and fire blight. Crucial contributing reasons are the uncertainty in map position of some genes and the lack of tightly linked markers suitable for high-throughput analysis (HTA) that reduces the costs of MAB. Single-nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…In the more studied crop, apple, an example of development of a set of reliable markers for MAS, SNPs, has been recently reported (Jänsch et al 2015). Eight loci, robustly associated with resistance to three diseases (apple scab, powdery mildew, and fire blight), were the focus of this work.…”
Section: Resultsmentioning
confidence: 99%
“…In the more studied crop, apple, an example of development of a set of reliable markers for MAS, SNPs, has been recently reported (Jänsch et al 2015). Eight loci, robustly associated with resistance to three diseases (apple scab, powdery mildew, and fire blight), were the focus of this work.…”
Section: Resultsmentioning
confidence: 99%
“…A study investigating QTLs associated with bud phenology in apple identified a candidate E3 ubiquitin protein encoding gene present as a tandem array of 14 copies in 'Golden Delicious', making it a putative CNV [49]. More recently, a study that was performed to design SNP markers for eight major disease resistance loci, encountered two problems that can be explained by the occurrence of CNV in these regions [51]. Firstly, for the Rvi2, Rvi4 and Rvi11 loci conferring resistance to apple scab (Venturia inaequalis), the presence of paralogs made it difficult to design primers for the SNPs linked to the respective loci, which amplified alleles only at the specific region of interest, without coamplifying the paralogous sequences.…”
Section: Discussionmentioning
confidence: 99%
“…This would be expected if resistance were conferred by the insertion of a segment of DNA, which contains the SNPs that failed to amplify, and is absent from susceptible individuals [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations